Teaching in the midst of the pandemic: Insights and perspectives from the lenses of the pre-service teachers - Romiro G. Bautista; Jamina G. Camayang (Institute of Advanced Engineering and Science, 2022)
The experiences of the pre-service teachers in their student teaching (ST) program are crucial as they bridge the divergence between their dependence to their cooperating teacher under the wings of their four-year teacher training program and their emancipatory leap towards autonomy in the field of actual teaching. This study was designed to document the experiences of the pre-service teachers in their pandemic ST for the school year 2020-2021. Describing their experiences and identifying factors contributing to their experiences are ways of analyzing this phenomenal issue in our educational state. Employing the qualitative research design using Phenomenology as point of inquiry, 18 pre-service teachers eloquently narrated their experiences in this pandemic education. The following experiences are documented: challenging and engaging, experiences are superficial, ST is best done via face-to-face, and ST is hopeless this pandemic. On the other hand, the known factors affecting the informants’ pandemic education experiences include poor internet connectivity, lack of gadgets, technological know-how, feedback is not enough, and inattentive, distracted students. Based on the foregoing results and on the parameters of this study, it is concluded that the pre-service teachers who had their ST in the school year 2020-2021 in a state university in the Philippines did not practice well as they were confronted with mounting roadblocks in optimizing their potentials in teaching. It is further recommended that a revision on the current framework of the program is necessary in order to fully optimize the learning experiences of pre-service teachers.